OPTIMIZATION OF OIL PALM EMPTY FRUIT BUNCH GRAFTED POLYVINYL ALCOHOL HYDROGEL BY TAGUCHI METHOD AND INVESTIGATION OF ITS METAL IONS ADSORPTION - JUN YONG, YAP (IRC, 2017)
Heavy metal pollution in wastewater is one of the major environmental issues nowadays. Hydrogel is a potential material to remove heavy metal ions through adsorption. The purpose of this research is to optimize the Oil Palm Empty Fruit Bunch grafted Polyvinyl Alcohol (OPEFB-g-PVA) hydrogel using Taguchi method at different parameters based on the water absorption capacity. L9 orthogonal array from Taguchi method was used to design the experiments based on the four parameters: reaction grafting temperature, amount of initiator, amount of crosslinking agent and amount of oil palm empty fruit bunch fiber. Then, experiment was conducted where OPEFB, crosslinking agent - N,N'-Methylenebisacrylamide (NMBA) and initiator – ammonium persulfate (APS) were added into PVA solution prepared according to the orthogonal array. The grafted hydrogels were immersed in water containing 16ppm copper ions for 48 hours. The water absorption capacity and copper ion adsorption capacity were studied. The maximum water absorption capacity obtained was 139.91%. The adsorption of copper ion from the aqueous solution was accessed by atomic absorption spectrometer (AAS). The highest copper ion adsorption capacity was 1.062 mg/g dry hydrogel. However, it was found that the hydrogel with higher water absorption capacity has lower copper ion adsorption capacity. Characterization of optimized OPEFB-g-PVA was studied using Mercury Intrusion Porosimetry (MIP).